Distribution of hydrogen peroxide and formaldehyde over Central Europe during the HOOVER project - T. Klippel; H. Fischer; H. Bozem; M. G. Lawrence; T. Butler; P. Jöckel; H. Tost; M. Martinez; H. Harder; E. Regelin; R. Sander; C. L. Schiller; et al. (Atmospheric Chemistry and Physics, 2011)
In this study we report measurements of hydrogen peroxide (H2O2), methyl hydroperoxide* (MHP* as a proxy of MHP based on an unspecific measurement of total organic peroxides) and formaldehyde (HCHO) from the HOx OVer EuRope (HOOVER) project (HOx = OH+HO2). HOOVER included two airborne field campaigns, in October 2006 and July 2007. Measurement flights were conducted from the base of operation Hohn (Germany, 54° N, 9° E) towards the Mediterranean and to the subpolar regions over Norway. We find negative concentration gradients with increasing latitude throughout the troposphere for H2O2 and CH3OOH*. In contrast, observed HCHO is almost homogeneously distributed over central and northern Europe and is elevated over the Mediterranean. In general, the measured gradients tend to be steepest entering the Mediterranean region, where we also find the highest abundances of the 3 species. Mixing ratios of these tracers generally decrease with altitude. H2O2 and CH3OOH* show maxima above the boundary layer at 2–5 km, being more distinct over southern than over northern Europe. We also present a comparison of our data with simulations by two global 3-D-models, MATCH-MPIC and EMAC, and with the box model CAABA. The models realistically represent altitude and latitude gradients for both HCHO and hydroperoxides (ROOH). In contrast, the models have problems reproducing the absolute mixing ratios, in particular of H2O2. Large uncertainties about retention coefficients and cloud microphysical parameters suggest that cloud scavenging might be a large source of error for the simulation of H2O2. A sensitivity study with EMAC shows a strong influence of cloud and precipitation scavenging on the budget of H2O2 as simulations improve significantly with this effect switched off.